Variation in COVID-19 Hospitalizations and Deaths Across New York City Boroughs - Rishi K. Wadhera; Priya Wadhera; Prakriti Gaba; José F. Figueroa; Karen E. Joynt Maddox; Robert W. Yeh; Changyu Shen (2020)
This study describes demographic characteristics and hospital bed capacities of the 5 New York City boroughs, and evaluates whether differences in testing for coronavirus disease 2019 (COVID-19), hospitalizations, and deaths have emerged as a signal of racial, ethnic, and financial disparities.